The Oral Language Proficiency of Indonesian English Teachers - Teguh Budiharso (IJELTAL (Indonesian Journal of English Language Teaching and Applied Linguistics), 2019)
This study reports an observation of the competencies of Indonesian secondary English teachers.  An intensive observation over a two-week workshop session was performed involving 38 English teachers, with this group comprising 18 SMP English teachers and 20 SMA English teachers. Three aspects of the observation were identified for this study: competence in oral English, competence in written discourse, and the ability to motivate students in the classroom. This study revealed that English teachers lacked practice in speaking, resulting in an insufficient mastery of the oral use of English. In written discourse, the teachers showed a lack of mastery with rhetoric and the linguistic aspects of writing.  In terms of strategies to motivate students in the classroom, the teachers generally lacked self-confidence